COMPARATIVE EVALUATION OF KETOPROFEN CREAM WITH DICLOFENAC AND PIROXICAM CREAM IN PATIENTS WITH RHEUMATOID ARTHRITIS DISORDERS: - Muhammad Razi Ullah Khan; Saeed Ur Rashid Nazir; Musaddique Hussain (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2015)
Non steroidal Anti- inflammatory drugs have their origin as the derivatives of plants, which were observed to have their therapeutic effects in different disease states. They have the advantage of local action without developing central adverse effects and cognitive impairments. Side effects have been well described, although partly neglected. Topical delivery of NSAID has its therapeutic applications in management of pain and inflammation in Rheumatoid arthritis patients. Rheumatoid arthritis is a chronic systemic inflammatory disorder that may affect many tissues and organs but principally attacks the synovial joints. It can be disabling and painful condition, which can lead to substantial loss of functioning and mobility if not adequately treated. The aim of the present investigation was to compare the Ketoprofen cream with Diclofenac and Piroxicam cream in a group of volunteers suffered from Rheumatoid arthritis and to compare the efficacy of these creams in reduction of inflammation. This single blind comparative study was done to determine the efficacy, tolerability and acceptability of topical application of Ketoprofen cream (1%w/w) vs diclofenac cream (1%w/w) and piroxicam cream (0.5%w/w) in Rheumatoid arthritis patients. In this study, one hundred and twenty five volunteers suffering with acute Rheumatoid arthritis and age group between 40-70 years were analyzed for assessing the intensity of pain and anti-inflammatory effects of these three creams. The study revealed that Ketoprofen cream provides a good level of pain relief removes swelling and tenderness and improves the functional impairment, without the systemic adverse events associated with oral NSAIDs.Key Words: Cream, Diclofenac, Ketoprofen, Piroxicam, Rheumatoid arthritis